Mittelosteuropäische Migrantinnen in Berlin: Transnationale Prozesse: Bildung, Erwerbstätigkeit, Familie - Jockenhövel-Schiecke, Helga (transcript, 2017)
Observation with participation, at times with active participation - empirical study about female migrants from Central Eastern Europe in Berlin, their motives for immigration and transnational education and work processes.